Enteric parasitic infections in children and dogs in resource-poor communities in northeastern Brazil: Identifying priority prevention and control areas. - Tatiani Vitor Harvey; Alice M Tang; Anaiá da Paixao Sevá; Camila Albano Dos Santos; Silvia Maria Santos Carvalho; Christiane Maria Barcellos Magalhães da Rocha; Bruno César Miranda Oliveira; George Rego Albuquerque (Public Library of Science (PLoS), 2020)
The aim of this study was to determine the prevalence and risk factors of the main enteric parasitic infections that affect children and dogs in the municipality of Ilhéus, Bahia, Brazil; and to identify the geopolitical areas that should receive priority interventions to combat them. Between March and November 2016, fecal samples of 143 dogs and 193 children aged 1 month to 5 years were collected in 40 rural and semirural communities using a systematic sampling approach, stratified by district. Samples were collected by legal guardians of the children and / or dog owners. Eggs, larvae, cysts and oocysts of parasites were concentrated by centrifugal-flotation and centrifugal-sedimentation, and acid-resistant staining was used to visualize parasites. One hundred and thirty-two children (68.4%), 111 dogs (77.6%) and 199 (73.7%) dog fecal samples collected from streets were parasitized. Giardiasis, cryptosporidiosis, amoeba infections and hookworm were the most frequent infections in all studied populations, in addition to trichuriasis in dogs and ascaridiasis in children. A predominance of Giardia and hookworms was observed in children and dogs, respectively. The coastal districts of Aritaguá, Olivença and the main district had a higher parasitic diversity and overlapping of important potential zoonotic infections. Age over one year (p<0.001), adjusted OR = 3.65; 95% CI = 1.86-7.16) and income below the minimum monthly salary (p = 0.02, adjusted OR = 2.78, 95% CI = 1.17-6.59) were the main factors associated with intestinal parasitic infections in children and dogs, respectively. The coastal districts of Aritaguá and Olivença and the main district should be prioritized through enteric disease control programs, and the factors associated with infections must be considered in the design of health interventions in these districts. The integration between affirmative income actions and investments to improve the health infrastructure of these communities may work more effectively than current preventive measures to combat enteric parasites.